Seizures Associated with Povidone-Iodine Impregnated Antral Pack in a Child: a Case Report and Review of Literature - Samuel Gbenga Adetunji; Oxoemene N Obuekwe; Stanley O Iyorzor; Mohammed Ibrahim Sani (Nigerian Dental Association, 2024)
This is a case of 11 years-old patient diagnosed of suppurative osteomyelitis of the right maxilla. He had incision and drainage with sequestrectomy under general anaesthesia, and povidone-iodine-impregnated antra pack. About 60 hours after surgery, patient began to have seizures, about 6 episodes on the first night, generalized, tonic-clonic, each lasting about 1 minute with post-ictal vomiting. An initial assessment of meningitis (to rule out cerebral abscess) was made. The seizure episodes which lasted for 3 days began to reduce gradually, and completely subsided 24 hours after the removal of the antra pack. However, when the patient had a CT scan with iodine-based contrast as requested by the paediatric neurologist (to rule out cerebral abscess), the episodes went up significantly again for another 24 hours, after which it began to reduce, till none was recorded 48 hours after contrast administration. Povidone-Iodine (PVI) slowly liberates free iodine to exhibit its broad range of microbicidal activity. However, depending on the amount of iodine absorbed, there is a possibility of iodine toxicity, with different systemic manifestations including seizures, especially in children. The seizure is believed to be a result of disruption in the blood-brain barrier by free iodine from PVI and the iodine-based contrast media. Therefore caution should be taken in using PVI as an antiseptic agent in antra packs or on any mucosa surface, especially in children.